German Americana : 1800 - 1955 ; a comprehensive bibliography of German, Austrian, and Swiss books and dissertations on the United States - Strupp, Christoph (Deutsches Historisches Institut Washington DC: Reference guides of the German Historical Institute Washington, D.C.;, 2005)
A comprehensive bibliography of books and scholarship on the United States produced in German-speaking countries since 1800.